Populasi Owa Jawa (Hylobates moloch) di Taman Nasional Gunung Gede Pangrango, Jawa Barat - Febriany Iskandar; Ani mardiastuti; Entang Iskandar; Randall C. Kyes (Jurnal Primatologi Indonesia, 2009)
This research was conducted in Gunung Gede Pangrango National Park and aimed to study javan gibbon population  and analyzing problems affecting the existence of the species. The total number of individuals were founded in this research were 42 individuals of 13 groups. The densities of javan gibbon at core zone were 7.14 individuals/km2 and 2.30 groups/km2, whereas at utilization zone were 5.69 individuals/km2 and 1.54 groups/km2. Estimated total individual density were 6.43 individu/km2 whereas group density were 1.93 groups/km2. The estimation of javan gibbon in Gunung Gede Pangrango National Park were 347 individuals in 105 groups. Several problems occured to the habitat and the population of javan gibbon in Gunung Gede Pangrango National Park were: (1) illegal logging; (2) agricultural lan dclearing; (3) tourists and other human activities; (4) illegal hunting; (5) firewoods gathering; (6) non-wood forest product extraction. There were three recommendations to ensure the conservation of javan gibbons in Gunung Gede Pangrango National Park: (1) enhancing the management of Gunung Gede Pangrango National Park areas; (2) managing the activities of local people; and (3) managing tourist program of Gunung Gede Pangrango National Park. Keywords: javan gibbon, population, National Park